Multi-institutional validation of brain metastasis velocity, a recently defined predictor of outcomes following stereotactic radiosurgery. (January 2020) - McTyre, Emory R.; Soike, Michael H.; Farris, Michael; Ayala-Peacock, Diandra N.; Hepel, Jaroslaw T.; Page, Brandi R.; Shen, Colette; Kleinberg, Lawrence; Contessa, Joseph N.; Corso, Christopher; Chiang, Veronica; Henson-Masters, Adrianna; et al.
Highlights: Brain metastasis velocity describes the recurrence rate of new brain metastases after initial treatment with radiosurgery. Brain metastasis velocity is calculated by dividing the number of new brain metastases after initial radiosurgery by the time in years since first radiosurgery. Patients can be stratified into high, intermediate, and low risk velocity groups, which corresponds with overall survival. The current study externally validates brain metastasis velocity as a prognosticator with over 700 patients from eight institutions. Brain metastasis velocity is being employed in clinical trials as a tool to stratify patients for salvage whole brain radiation and radiosurgery. Abstract: Introduction: Brain metastasis velocity (BMV) is a prognostic metric that describes the recurrence rate of new brain metastases after initial treatment with radiosurgery (SRS). We have previously risk stratified patients into high, intermediate, and low-risk BMV groups, which correlates with overall survival (OS). We sought to externally validate BMV in a multi-institutional setting. Methods: Patients from nine academic centers were treated with upfront SRS; the validation cohort consisted of data from eight institutions not previously used to define BMV. Patients were classified by BMV into low (<4 BMV), intermediate (4–13 BMV), and high-risk groups (>13 BMV). Time-to-event outcomes were estimated using the Kaplan–Meier method. Cox proportional hazards methods were used to estimate the effect of BMV and salvage modality on OS. Results: Of 2829 patients, 2092 patients were included in the validation dataset. Of these, 921 (44.0%) experienced distant brain failure (DBF). Median OS from initial SRS was 11.2 mo. Median OS for BMV < 4, BMV 4–13, and BMV > 13 were 12.5 mo, 7.0 mo, and 4.6 mo ( p < 0.0001). After multivariate regression modeling, melanoma histology ( β : 10.10, SE: 1.89, p < 0.0001) and number of initial brain metastases ( β : 1.52, SE: 0.34, p < 0.0001) remained predictive of BMV (adjusted R 2 = 0.06). Conclusions: This multi-institutional dataset validates BMV as a predictor of OS following initial SRS. BMV is being utilized in upcoming multi-institutional randomized controlled trials as a stratification variable for salvage whole brain radiation versus salvage SRS after DBF.